1992
DOI: 10.1111/j.1469-8137.1992.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone and acidic fog on red spruce needle epicuticular wax production, chemical composition, cuticular membrane ultrastructure and needle wettability

Abstract: SUMMARYOne-year-old red spruce {Picea rubens Sarg.) seedlings were exposed, from bud break, to ozone (O,,) and acidic fog for 14, 42 or 77 days. Ozone was more damaging than acidic fog to epicuticular wax. Wax quantity on needles exposed to charcoal-filtered air (CFA) and pH 4-2 fog (control) increased from 14 to 42 days, but decreased by 77 days. Exposure of elongating needles to 70 ppb O3 and pH 4-2 fog reduced tbe rate of de novo wax syntbesis. Red spruce wax is composed of secondary alcobols (50 °o), nonac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…1), and\or the sequence of class deposition onto the needle surface would be expected to play a role in the degree of biosynthetic response, and overall sensitivity of the cuticle to u.v.-B radiation. This has been clearly shown to be the case for needle wax response to other components of the changing atmospheric environment such as acid rain (Percy & Baker, 1990), acid vapour (Bytnerowicz et al, 1997, tropospheric ozone\acid fog (Percy, Jensen & McQuattie, 1992), or general pollution climate (Turunen et al, 1997 ;Cape & Percy, 1997). Response to changes in plant growth environment such as light quantity\quality (Cape & Percy, 1993) is also known to be influenced by shoot phenology in the four species studied here.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…1), and\or the sequence of class deposition onto the needle surface would be expected to play a role in the degree of biosynthetic response, and overall sensitivity of the cuticle to u.v.-B radiation. This has been clearly shown to be the case for needle wax response to other components of the changing atmospheric environment such as acid rain (Percy & Baker, 1990), acid vapour (Bytnerowicz et al, 1997, tropospheric ozone\acid fog (Percy, Jensen & McQuattie, 1992), or general pollution climate (Turunen et al, 1997 ;Cape & Percy, 1997). Response to changes in plant growth environment such as light quantity\quality (Cape & Percy, 1993) is also known to be influenced by shoot phenology in the four species studied here.…”
Section: mentioning
confidence: 99%
“…Of particular concern would be the interaction of increased u.v.-B with co-occurring air pollutants such as ozone\acid fog (Percy et al, 1992), acid rain (Percy & Baker, 1990) or mixtures of drydeposited and wet-deposited pollutants (Cape & Percy, 1997) known to alter spruce needle wax chemical composition. Even subtle changes to needle physico-chemical characteristics might result in altered micro flora\pathogen interactions, needle water loss patterns, foliar uptake rates and early needle abscission.…”
Section: mentioning
confidence: 99%
“…Investigations have been performed on the impacts of fog on plants, such as the red spruce [108] and beech [109], as well as on hypolithic microbial communities [101,110]. Percy et al [108] reported that red spruce exposure to pH 4.2 acid fog increased wax quantity for a certain period, but a longer exposure decreased it; reduced the rate of de novo wax synthesis; changed the composition of wax reducing production of secondary alcohols (pH 3.0 fog).…”
Section: Impacts Of Fog On Plants and Microorganismsmentioning
confidence: 99%
“…Percy et al [108] reported that red spruce exposure to pH 4.2 acid fog increased wax quantity for a certain period, but a longer exposure decreased it; reduced the rate of de novo wax synthesis; changed the composition of wax reducing production of secondary alcohols (pH 3.0 fog). Acidic fogs also influence the cuticular membrane thickness and wettability of needles.…”
Section: Impacts Of Fog On Plants and Microorganismsmentioning
confidence: 99%
“…All these studies have in common that a more or less evident alteration of ,^^^ surface wax aggregates can be observed by scanning electron microscopy (Huttunen & Laine, 1983 ;Barnes, Davison & Booth, 1988;Bermadinger, Grill & Golob, 1988;Adams, Capron & Hutchinson, 1990;Percy & Baker, 1990). As a consequetice, leaf surface wettability increased as measured by the means of contact angle determination (Cape, 1983;Percy, Jensen & McQuattie, 1992). Besides many other factors, these changes of leaf surface properties are also believed to be involved in the occurrence of novel forest decline (Elstner & Osswald, 1984;Schulze, 1989) observed during the last decade in Western Europe (Blank.…”
mentioning
confidence: 99%